Attitudes towards using augmented reality in corporate training: A case study - Güner, Nilay. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
In today's rapidly changing world, trainers are required to develop themselves for using technology in their trainings to reach the new generation's needs, and Augmented Reality (AR) is one of the novelties coming with developing technology. Many researches show the benefits of AR usage in education but there are limited studies for corporate trainings. Increasing the use of AR in corporate trainings exactly depends on the development of internal trainers. This study aims to investigate the knowledge level and attitudes of internal trainers about AR usage in education. Based on this purpose, a case study was undertaken with 61 people in a corporate retail company, Turkey. Participants attended to a training session about AR, started with an awareness survey and finished with evaluation survey and interviews. Theoretical model of this study is based on Technology Acceptance Model (TAM). The hypotheses are tested by paired samples t-test, regression, ANOVA and independent samples t-test analysis. The results showed that after two-hours training and application session, almost all participants liked the whole AR experience and found it “beneficial”, “funny”, “engaging”, “interacting”, “creative” and “motivating” for educational use. They have also intended to use AR in their trainings. The other new implications are the suggestions of internal trainers for AR usage examples in different training types and for the development of AR platforms or applications. There are some other findings supporting previous studies. As a result, the future of AR usage in corporate trainings looks bright.
Keywords: Augmented reality.